Tata kelola yang transparan membangun asas-asas keterbukaan dalam pembentukan Peraturan Perundang-undangan - Rohinun, Fitria Nur Afifatur (Maliki Interdisciplinary Journal, 2024)
A democratic country is represented by the creation of laws and regulations based on its historical context. It is clear from the explanation of Article 5 Letter G that the causal principle means that all legal and regulatory processes must be open to all levels of society and transparent. However, in reality the process of developing laws and regulations in Indonesia currently seems rushed and hampers public participation. Even though the community plays a key role in the process of forming statutory regulations, this is because it is the community who will obey, implement and implement the provisions of these statutory regulations. This research uses a legislative approach to examine the type of normative juridical research, the types of legal materials used, especially primary, secondary and tertiary legal elements. Based on the results of research and analysis of openness problems, the basic regulations for the formation of laws in Indonesian positive law contain provisions that underlie the principles of regulating the principles of openness in the formulation of good laws and the availability of information on the implementation of the Establishment Laws for all levels of society, but not strictly speaking. comprehensive. as well as the widest opportunity for all levels of society to participate in the formation of laws in accordance with the general principles of good governance and the principles governing the formation of laws.